2019
DOI: 10.1177/0972150918811487
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effect of Management Support on the Relationship Between HR Practices and Employee Performance in Nigeria

Abstract: Given that management support and decisions do influence all the aspects of organization, this study investigates moderating effect of management support on the relationship between recruitment and selection, training and development, compensation, performance appraisal and succession planning and employee performance. The cross-sectional survey approach was used in which data were collected from 450 academics in the state-owned polytechnics in Nigeria. The partial least squares method (PLS) algorithm and boot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 57 publications
2
28
0
2
Order By: Relevance
“…For example, in a meta-analysis, Combs et al (2006) found that the relationship between HRM practices and outcomes is more robust in manufacturing companies when compared to service organizations. In a recent study conducted in Nigeria, researchers found that HRM practices (recruitment and selection, training and development, performance appraisal and succession planning) are positively associated with employee performance (Ismail et al, 2021). In a study conducted in India, Nigam et al (2011) found that the effectiveness of HR practices is contingent on the strategy implemented in the service sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a meta-analysis, Combs et al (2006) found that the relationship between HRM practices and outcomes is more robust in manufacturing companies when compared to service organizations. In a recent study conducted in Nigeria, researchers found that HRM practices (recruitment and selection, training and development, performance appraisal and succession planning) are positively associated with employee performance (Ismail et al, 2021). In a study conducted in India, Nigam et al (2011) found that the effectiveness of HR practices is contingent on the strategy implemented in the service sector.…”
Section: Introductionmentioning
confidence: 99%
“…For the past seven decades, several researchers have examined the influence of human resource management (HRM) practices on organizational performance (Becker & Gerhart, 1996;Boselie, 2014;Delaney & Huselid, 1996;Ehrlich, 1994;Figueiredo et al, 2016;Gope et al, 2018;Ismail et al, 2021). There has been a consensus among researchers that HRM practices help organizations achieve goals such as employee well-being, productivity, reducing employee turnover and increasing commitment (Beer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of empirical studies have been focused on the numerous antecedents of work engagement (WE) (for a recent meta-analysis review, see [2]). However, human resource management (HRM) practices as an antecedent of work engagement have been rarely investigated [3,4]. HRM practices refers to those practices that have the potential to improve and sustain organizational performance [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, human resource management (HRM) practices as an antecedent of work engagement have been rarely investigated [3,4]. HRM practices refers to those practices that have the potential to improve and sustain organizational performance [3][4][5]. These practices may be identified as a function of the performance outcome wanted by the organization.…”
Section: Introductionmentioning
confidence: 99%
“…The results found that the practice of HR such as compensation, performance appraisal will be effective in improving employee performance if mediated by management support. Furthermore, Ismail et al (2019) found that management support to strengthen the effectiveness of their human resources practices to performance. Meanwhile, Pham et al (2016) gets the results of the management support has a direct influence positively to organizational commitment and employee performance.…”
Section: Introductionmentioning
confidence: 99%